2000
DOI: 10.1074/jbc.m909946199
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Protein Domains of the Yeast Golgi GDP-mannose Transporter Mediate Oligomer Assembly and Export from the Endoplasmic Reticulum

Abstract: The substrates for glycan synthesis in the lumen of the Golgi are nucleotide sugars that must be transported from the cytosol by specific membrane-bound transporters. The principal nucleotide sugar used for glycosylation in the Golgi of the yeast Saccharomyces cerevisiae is GDP-mannose, whose lumenal transport is mediated by the VRG4 gene product. As the sole provider of lumenal mannose, the Vrg4 protein functions as a key regulator of glycosylation in the yeast Golgi. We have undertaken a functional analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(93 citation statements)
references
References 45 publications
4
87
0
2
Order By: Relevance
“…Previously we had shown that microsomal preparations of this yeast have only two endogenous nucleotide sugar transport activities, those for UDP-glucose and GDP-mannose (24,25). This facilitates assays of nucleotide sugar transport when a putative nucleotide sugar transporter from a different species is expressed in S. cerevisiae.…”
Section: Co3h52 Transports Udp-glcnac and Udp-galnacmentioning
confidence: 99%
“…Previously we had shown that microsomal preparations of this yeast have only two endogenous nucleotide sugar transport activities, those for UDP-glucose and GDP-mannose (24,25). This facilitates assays of nucleotide sugar transport when a putative nucleotide sugar transporter from a different species is expressed in S. cerevisiae.…”
Section: Co3h52 Transports Udp-glcnac and Udp-galnacmentioning
confidence: 99%
“…This protein forms homodimers (Abe et al 1999;Gao and Dean, 2000), shows a wide distribution in the Golgi, and contains a GALNK motif involved in GDP--Man binding (Gao et al 2001). Gda1 and Ynd1.…”
Section: Gdp--man Transportmentioning
confidence: 99%
“…Evidence is accumulating that NSTs in the active state are dimers (15)(16)(17)(18) or higher order complexes (19). In the case of the yeast GDP-mannose transporter, the C-terminal span seems to be essential for the formation of the dimer, while the N-terminal cytosolic tail is required for export from the ER (15,18). In contrast, the cytosolically located N-and C-terminal tails of murine UGT were found to be dispensable.…”
mentioning
confidence: 99%
“…Membrane topology has been determined for the murine CMP-sialic acid transporter (CST) and, in contrast to the theoretically predicted eight transmembrane domains, it was shown to contain 10 transmembrane domains (14). Evidence is accumulating that NSTs in the active state are dimers (15)(16)(17)(18) or higher order complexes (19). In the case of the yeast GDP-mannose transporter, the C-terminal span seems to be essential for the formation of the dimer, while the N-terminal cytosolic tail is required for export from the ER (15,18).…”
mentioning
confidence: 99%